Lack of committment or lack of resources? Owner-managers' attitudes towards training provision within the UK small firms / Syeda-Masooda Mukhtar - Mukhtar, Syeda-Masooda (Faculty of Business and Management ; UiTM Press, 2000)
In the knowledge-based global economy of the 21st century, investment in human capital will be critical in ensuring business survival and competitiveness. Yet, as we approach the new millennium, it is often frustrating to observe that while small businesses continue to complain of skills gaps, committing resources to training has never featured prominently on their agenda. This study sets out to explore this apparent paradox. In particular, the attitudes of small business owners-managers are analysed since it is their ethos and perspective that is critical in determining the strategic direction of training within their firms. The sample constitutes 144 UK firms.